The effect of coefficient of friction between rail vehicle wheels and rail track on operation power consumption - Mahamudin, Nur Shahibrahim; Darsivan, Fadly Jashi (Kulliyyah of Engineering (KOE), IIUM, 2023)
The daily cost of rail operation is increasing due to increased rail network size. Therefore, reducing operation power consumption is important for rail operators to optimize daily operation costs. Operation power consumption in rail operation can be divided into 80% traction power, such as vehicle propulsion system, and 20% non-traction power, such as station electrical consumption. Much research has already been conducted on advanced traction systems, such as regenerative braking storage systems, hybrid batteries, and others, which aim to reduce operation power consumption. However, very few address the concern about track condition and maintenance. This research focuses on the interaction between the rail vehicle wheels and the rail track and how the coefficient of friction affects the rail operation power consumption. As rail grinding is an essential rail preventive maintenance to improve track surface, the indirect coefficient of friction has shown an improvement that reduces rail operation power consumption. Train resistance can be expressed in the Davis equation, which is the mathematical model used in rail industries to find train performance. Our findings indicate that the application of the rail grinding method had successfully reduced the track kinetic coefficient of friction, reducing 9% in operation power consumption.